Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a/ Ta có: 27x : 3x = 9
=> 33x-x = 9 =\(\left(\pm3\right)^2\)
=> 3x - x = 2
=> 2x = 2
=> x = 1
Vậy x = 1
b/ Ta có:
1/2 . 2x + 4 . 2x = 9 . 25
=> 2x . ( 1/2 + 4 ) = 9 . 32
=> 2x . 9/2 = 288
=> 2x = 64
=> x = 32
Vậy x = 32
a ) 27x : 3x = 9
<=> ( 27 : 3 )x = 9
<=> 9x = 9
=> x = 1
b )\(\frac{1}{2}.2x+4.2x=9.2^5\)
<=> x + 8x = 9.32
<=> 9x = 288
=> x = 288 : 9 = 32
a) \(4^{x+3}-248=2^{x+1}\)
\(\Leftrightarrow2^{2x+6}-248=2^{x+1}\)
\(\Leftrightarrow2^{2x+6}-2^{x+1}=248\)
\(\Leftrightarrow2^{x+1}\left(2^{x+5}-1\right)=248=2^3.31=2^2.62=2.124=1.248\)
Thay vào nha
Ta có : \(\left(2x+3\right)\left(x-7\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}2x+3=0\\x-7=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}2x=-3\\x=7\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=-\frac{3}{2}\\x=7\end{cases}}\)
a: =>|7x-9|=5x-3
\(\Leftrightarrow\left\{{}\begin{matrix}x>=\dfrac{3}{5}\\\left(7x-9-5x+3\right)\left(7x-9+5x-3\right)=0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x>=\dfrac{3}{5}\\\left(2x-6\right)\left(12x-12\right)=0\end{matrix}\right.\Leftrightarrow x\in\left\{3;1\right\}\)
b: =>|17x-5|=|17x+5|
=>17x-5=17x+5(vô lý) hoặc 17x-5=-17x-5
=>34x=0
hay x=0
c: =>|3x+4|=|4x-18|
=>4x-18=3x+4 hoặc 4x-18=-3x-4
=>x=22 hoặc 7x=14
=>x=22 hoặc x=2
TÌM X:
a) 2x - 3 = \(\frac{1}{2}\)
2x = \(\frac{1}{2}+3\)
2x = \(\frac{7}{2}\)
x = 2 : \(\frac{7}{2}\)
x = 2 . \(\frac{2}{7}\)
x = \(\frac{4}{7}\)
b) /x+1/ = 0.25
/x+1/ = \(\frac{1}{4}\)
\(\orbr{\begin{cases}x+1=\frac{1}{4}\\x+1=-\frac{1}{4}\end{cases}}\)
\(\orbr{\begin{cases}x=\frac{1}{4}-1\\x=-\frac{1}{4}-1\end{cases}}\)
\(\orbr{\begin{cases}x=-\frac{3}{4}\\x=-\frac{5}{4}\end{cases}}\)
c) 32 : 2x = 2
\(2x=32:2\)
\(2x=16\)
\(x=16:2\)
\(x=8\)
~GOOD STUDY~
a) \(\Leftrightarrow\left|2x-3\right|=\frac{1}{4}\Leftrightarrow\orbr{\begin{cases}x\ge\frac{3}{2}\mid:2x-3=\frac{1}{4}\Rightarrow2x=\frac{13}{4}\Rightarrow x=\frac{13}{8}\left(TM\right)\\x< \frac{3}{2}\mid:3-2x=\frac{1}{4}\Rightarrow2x=\frac{11}{4}\Rightarrow x=\frac{11}{8}\left(TM\right)\end{cases}.}\)
b) \(\Leftrightarrow\left|x-1\right|=\frac{3}{4}\Leftrightarrow\orbr{\begin{cases}x\ge1\mid:x-1=\frac{3}{4}\Rightarrow x=\frac{7}{4}\left(TM\right)\\x< 1\mid:1-x=\frac{3}{4}=>x=\frac{1}{4}\left(TM\right)\end{cases}}\)
c) \(\frac{3}{5\left(x-\frac{5}{6}\right)}-\frac{1}{2\left(\frac{3}{2}-1\right)}=-\frac{1}{4}\Leftrightarrow\frac{3}{\frac{5\left(6x-5\right)}{6}}-\frac{1}{2\cdot\frac{1}{2}}=-\frac{1}{4}\Leftrightarrow\frac{18}{5\left(6x-5\right)}=-\frac{1}{4}+1\)
\(\Leftrightarrow\frac{18}{5\left(6x-5\right)}=\frac{3}{4}\Leftrightarrow6x-5=\frac{24}{5}\Leftrightarrow6x=\frac{49}{5}\Leftrightarrow x=\frac{49}{30}\)
d) \(\frac{1}{3}+\frac{1}{6}+\frac{1}{10}+...+\frac{2}{x\left(x+1\right)}=\frac{2015}{2016}\)
\(\Leftrightarrow\frac{2}{2\cdot3}+\frac{2}{3\cdot4}+\frac{2}{4\cdot5}+...+\frac{2}{x\left(x+1\right)}=\frac{2015}{2016}\)
\(\Leftrightarrow2\cdot\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+...+\frac{1}{x}-\frac{1}{x+1}\right)=\frac{2015}{2016}\)
\(\Leftrightarrow2\left(\frac{1}{2}-\frac{1}{x+1}\right)=\frac{2015}{2016}\Leftrightarrow2\cdot\frac{x+1-2}{2\left(x+1\right)}=\frac{2015}{2016}\Leftrightarrow\frac{x-1}{x+1}=\frac{2015}{2016}\)
\(\Leftrightarrow2016x-2016=2015x+2015\Leftrightarrow x=2015+2016=4031\)
Vậy x = 4031.
(2x-1)^3=8^3
2x-1=8
2x=9
x=9/2
tich minh nha
\(\left(2x-1\right)^3=2^9=\left(2^3\right)^3\)
=> 2x-1=23
=> 2x = 23 + 1
=> 2x = 9
=> x = 9/2